Economic Efficiency of the Norms of Rice, Domestic and Ore Fertilizers Used in the Production of Autumn Wheat - Turdaliyev Avazbek Turdalievich; Mamadaliyev Muhammadkarim Zoyirjon ogli (Zien Journals, 2023)
This article describes the results of research on the economic effectiveness of rice straw, local and mineral fertilizer standards used in winter wheat care. According to it, it was determined that 73.4% yield can be achieved by feeding winter wheat with rice straw at the rate of 20 t/ha of manure and mineral fertilizers at the rate of N100P75K50 kg/ha
Keywords: winter wheat; rice straw; mineral fertilizers